Pengaruh Persepsi Dan Preferensi Konsumen Terhadap Keputusan Menginap Di Hotel Syariah Sumatera Utara - Nidya Fabianti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study was conducted in order to understand the influence of consumer perceptions and preferences on the decision to stay at a sharia hotel in North Sumatra. The type of research used is quantitative research using a mixed system. Data collection used is by distributing questionnaires and using a Likert scale as a medium for measuring respondents' responses. The number of respondents in this study was 96 people who were selected using Cluster random sampling. This study uses multiple linear regression analysis, then the technical processing of data analysis uses the SPSS version 26 application.